An Act for Regulating the Militia of the Province of Maryland (MD General Assembly, Lower House, L.H.J. Liber No. 48, Assembly Proceedings, May 22, 1756) - (:unkn) unknown (General Publisher, 1756)
Prohibited the sale of strong liquor within five miles of any place of militia training.
--
Keywords: ARMED FORCES